1017 An Integrated Behavioral Therapy for Positive Airway Pressure Adherence and Insomnia Reduces Nocturia Frequency. (27th May 2020) - Fung, C H; Martin, J L; Dzierzewski, J M; Fiorentino, L; Stepnowsky, C; Song, Y; Zeidler, M; Mitchell, M; Vaughan, E C; Huang, A; Markland, A; Josephson, K; et al.
Abstract: Introduction: Nocturia is common among patients with both insomnia disorder and obstructive sleep apnea (OSA) and adversely affects quality of life. Within a randomized controlled trial testing an integrated behavioral therapy for positive airway pressure (PAP) adherence and insomnia for patients with coexisting OSA and insomnia disorder, we examined the impact of the integrated therapy on nocturia frequency. Methods: Patients aged > 50 years with untreated OSA (apnea hypopnea index > 15) and chronic insomnia disorder were recruited from a VA medical center and randomized to 5 weekly individual integrated behavioral treatment sessions versus control (general sleep education). Nocturia frequency (self-reported average number of nocturia events per night) was assessed at baseline, 3 months, and 6 months. Linear regression models were used to examine relationships between objective PAP adherence (# nights used > 4hrs over the last 30 days) and Insomnia Severity Index (ISI) score (0 [none] - 28 [severe]) and nocturia frequency (0 - 5+/night), and change in nocturia frequency associated with integrated therapy. Results: Nocturia data were available for 112 participants (treatment=56, control=56; mean age 63 [SD 7], 95% male). Mean nocturia frequency (episodes/night) was 2.1 (SD 1.3; baseline), 1.6 (SD 1.1; 3 months), and 1.7 (SD 1.2; 6 months). Overall, higher PAP adherence (B=.029, p=.008) and ISI score improvement (B=0.05, p=.004) were associated with decreased nocturia frequency at 3-month follow-up. No differences were observed in nocturia frequency between treatment and control participants at baseline (p=.429). Integrated therapy reduced nocturia frequency at 3 months (B=-0.56, p=.020) but not at 6 months follow-up (B=-0.4, p=.081) compared to control. Conclusion: Nocturia frequency improved with integrated behavioral therapy for PAP adherence and insomnia in veterans (primarily male) with co-existing OSA and insomnia. Additional studies are needed to examine the mechanisms underlying the relationship between the behavioral therapy for PAP adherence and insomnia and nocturia. Support: VA HSR&D; NIA; VA GRECC